Why we need more collaboration in Europe to enhance post-marketing surveillance of vaccines. (22nd December 2020) - Sturkenboom, Miriam; Bahri, Priya; Chiucchiuini, Antonella; Grove Krause, Tyra; Hahné, Susan; Khromava, Alena; Kokki, Maarit; Kramarz, Piotr; Kurz, Xavier; Larson, Heidi J.; de Lusignan, Simon; Mahy, Patrick; et al.
Highlights: Europe needs a sustainable system for timely, high-quality evidence on vaccine benefits and risks. European vaccine stakeholders have different perspectives but similar information needs. The ADVANCE project (now VAC4EU) has developed and tested a system to generate the necessary evidence. Abstract: The influenza A/H1N1 pandemic in 2009 taught us that the monitoring of vaccine benefits and risks in Europe had potential for improvement if different public and private stakeholders would collaborate better (public health institutes (PHIs), regulatory authorities, research institutes, vaccine manufacturers). The Innovative Medicines Initiative (IMI) subsequently issued a competitive call to establish a public-private partnership to build and test a novel system for monitoring vaccine benefits and risks in Europe. The ADVANCE project (Accelerated Development of Vaccine benefit-risk Collaboration in Europe) was created as a result. The objective of this paper is to describe the perspectives of key stakeholder groups of the ADVANCE consortium for vaccine benefit-risk monitoring and their views on how to build a European system addressing the needs and challenges of such monitoring. These perspectives and needs were assessed at the start of the ADVANCE project by the European Medicines Agency together with representatives of the main stakeholders in the field of vaccines within and outside the ADVANCE consortium (i.e. research institutes, public health institutes, medicines regulatory authorities, vaccine manufacturers, patient associations). Although all stakeholder representatives stated they conduct vaccine benefit-risk monitoring according to their own remit, needs and obligations, they are faced with similar challenges and needs for improved collaboration. A robust, rapid system yielding high-quality information on the benefits and risks of vaccines would therefore support their decision making. ADVANCE has developed such a system and has tested its performance in a series of proof of concept (POC) studies. The system, how it was used and the results from the POC studies are described in the papers in this supplementary issue.